Dampak Pariwisata Terhadap Peningkatan Kesejahteraan Pelaku UMKM di Desa Penglipuran Kabupaten Bangli - Dewi, Ni Wayan Sri Cintya; Meitriana, Made Ary (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the impact of tourism on improving the welfare of MSME actors in Penglipuran Village, Bangli Regency. This research uses a qualitative approach. In the data collection process, researchers used purposive sampling with the subject of the research being the community of MSME actors in Penglipuran Village. The number of informants in this study was 15 informants. The data collection method used in the study used observation, interview, and documentation methods. The data analysis technique used is the Miles and Huberman model data analysis, where activities in data analysis are starting from data collection, reducing data, presenting data, and drawing conclusions. The results showed that the existence of tourism had a positive impact on improving the welfare of MSME actors in Penglipuran Village.